Flavorful Words: The Analysis of Linguistic Landscape on Restaurant Menus in Pererenan and Canggu - Setiari, Ni Kadek Ayu Wulan; Utami, Ni Made Verayanti (Lingua Cultura, 2024)
The research aimed to determine the linguistic landscape, especially the menu lists displayed by restaurants around Pererenan and Canggu, and to explain the linguistic patterns and trends in restaurant menu names, including using one or more languages. The research used a descriptive qualitative method with analysis of language code types using the theory of Landry and Bourhis, who analyzed the form of language code types in the linguistic landscape. The approach used was mixed, which included primary and secondary data collection methods. Primary data were collected through direct observation and field research involving a comprehensive survey of all restaurant businesses around Pererenan and Canggu. The findings show that there are many restaurant menu names that use a mixture of Bahasa and English, as from the data on restaurant menu names in Parerenan district are Kunyit Asam Tonic, Lettuce Bakar, Sate Platter, Ice Roti, King Kelapa, and restaurant menu names from Canggu are Madu Iced Tea, Toast Manis, Nelayan Energy, Pepes Ikan Indonesia, etc. Thus, there are 27 restaurant menu lists in Parerenan and Canggu. This restaurant menu lists uses a mixture of local and international languages. There are also restaurant menus that use a mixture of regional languages (Balinese) and English. Combining these two languages is a good strategy for restaurants to attract customers.